Design of an adaptive finger with encompassing grasp capability for parallel grippers - Kok, Yuan Yik (2019)
Adaptive grasping was an emerging technology due to the demand to fulfil the task requirement of having one robotic picker to cope with items of variable geometry attributes. The parallel gripper was widely and commonly used in robotic automation because of its simple one DOF mechanism. Thus, the motivation was to enable parallel gripper to perform adaptive grasping. The thesis presented the design of an underactuated adaptive finger for the standard parallel gripper. Adaptive finger mechanisms were surveyed, reviewed, and kinematics for adaptive grasping were studied to design a novel mechanism for parallel grasping. Experiments show parallel gripper attached with the adaptive finger could form pinching and encompassing grasp, which fulfilled the capabilities of an adaptive gripper. The adaptive fingers demonstrated that when performing encompassing grasp, it forms three to six contact points on objects with regular and irregular shapes.